Performances of two rapid LAMP-based techniques for the intrapartum detection of Group B Streptococcus vaginal colonization - Rym Charfi; Cécile Guyonnet; Meiggie Untrau; Gaëlle Giacometti; Thierry Paper; Claire Poyart; Céline Plainvert; Asmaa Tazi (BMC, 2024)
Abstract Purpose Group B Streptococcus (GBS) is the leading cause of invasive infections in newborns. The prevention of GBS neonatal disease relies on the administration of an intrapartum antibiotic prophylaxis to GBS-colonized women. In recent years, rapid intrapartum detection of GBS vaginal colonization using real-time nucleic acid amplification tests (NAATs) emerged as an alternative to antenatal culture screening methods. Methods We compared the performances of two loop-mediated isothermal amplification (LAMP) tests, the Ampliflash® GBS and the PlusLife® GBS tests, to standard culture for GBS detection in vaginal specimens from pregnant women. The study was conducted from April to July 2023 in a French hospital of the Paris area. Results A total of 303 samples were analyzed, including 85 culture-positive samples (28.1%). The Ampliflash® GBS test and the PlusLife® GBS tests gave a result for 100% and 96.3% tests, respectively. The performances of the tests were as follows: sensitivity 87.1% (95% confidence interval (CI) 78.3-92.6) and 98.7% (95% CI 93.0-99.8), specificity 99.1% (95% CI 96.7-99.8), and 91.9% (95% CI 87.3-95.0), respectively. False negative results of the Ampliflash® GBS test correlated with low-density GBS cultures. Time-to-results correlated with GBS culture density only for the PlusLife® GBS test (p < 0.001). Conclusion Both techniques provide excellent analytical performances with high sensitivity and specificity together with a short turnaround time and results available in 10 to 35 min. Their potential to further reduce the burden of GBS neonatal disease compared with antenatal culture screening needs to be assessed in future clinical studies.